Analysis of visual elements in Barbie movie posters - Wa Ode, Rosyta Pua (COMMICAST, 2023)
As a means of promoting a movie, posters are usually short, clear, concise, and attention-grabbing, and visual elements such as illustrations of movie scenes are dominant. The meaning of a movie poster is formed through visual elements in such a way. The analysis conducted on this Barbie poster aims to find out the cause of the elements in this Barbie poster. This research uses qualitative research methods with descriptive analysis. In this research, most of the data collected are in the form of images, words and sentences where these data have meaning and can achieve a more real understanding than numbers or frequencies. To collect data for this research, researchers used observation and recording techniques. The typography used on the "Barbie" poster is Bartex font. The visuals on the Barbie poster are Barbie and Ken. The blue color on the poster illustrates the meaning of loyalty and trust in the characters in the Barbie movie. The use of pink in this Barbie poster is because Barbie is always synonymous with pink, the pink color also describes feminism in Barbie. The layout used in this Barbie movie poster is symmetrical, meaning that the visual weight of the design elements is spread evenly horizontally, vertically, and radially. From the explanation above we can conclude that movie posters play an important role in promoting this Barbie movie, as for the analysis carried out on this Barbie poster aims to find out what is caused by the elements in this Barbie poster.